Socialism in Economic Research in the Age of Globalization, Sustainability, and Digitalization: A Theory–Context–Method Systematic Review - Pratama, Himawan Aditya; Rini, Ika Tirta Candra; Iqbal, Muhammad (Electronic Journal of Education, Social Economics and Technology, 2025)
This study presents a PRISMA-guided systematic literature review of 39 Scopus-indexed journal articles published between 2015 and 2025 on socialism in economic systems in the era of globalization, sustainability, and digitalization. Using an integrative Theory–Context–Method (TCM) framework combined with thematic analysis, the review maps how contemporary scholarship mobilizes institutionalist, political economy, and Marxist perspectives across diverse contexts, particularly post-socialist Europe, China, and global socialism debates. The findings show that research is conceptually anchored in comparisons between socialism and capitalism, empirically concentrated on socialist economic reform, post-socialist transitions, and socialist legacy effects, and methodologically dominated by qualitative and case-based designs supplemented by quantitative studies. Global market integration, ideological conflict, and enduring institutional legacies emerge as the core explanatory triangle, while sustainability and digitalization appear mainly as emerging pressures rather than fully theorized mechanisms. The review contributes by uncovering the tight coupling between theory, context, and method that structures cumulative knowledge on socialism, and by proposing a future research agenda that prioritizes cross-context theory deployment, mixed-method designs, and the integration of sustainability and digitalization as central causal mechanisms in analyses of socialist-oriented economic governance.